Ending Neglect: The Elimination of Tuberculosis in the United States - Institute of Medicine (The National Academies Press, 2000)
Tuberculosis emerged as an epidemic in the 1600s, began to decline as sanitation improved in the 19th century, and retreated further when effective therapy was developed in the 1950s. TB was virtually forgotten until a recent resurgence in the U.S. and around the world2014ominously, in forms resistant to commonly used medicines. What must the nation do to eliminate TB? The distinguished committee from the Institute of Medicine offers recommendations in the key areas of epidemiology and prevention, diagnosis and treatment, funding and organization of public initiatives, and the U.S. role worldwide. The panel also focuses on how to mobilize policy makers and the public to effective action. The book provides important background on the pathology of tuberculosis, its history and status in the U.S., and the public and private response. The committee explains how the U.S. can act with both self-interest and humanitarianism in addressing the worldwide incidence of TB.

The Hidden Epidemic: Confronting Sexually Transmitted Diseases - Institute of Medicine
The United States has the dubious distinction of leading the industrialized world in overall rates of sexually transmitted diseases (STDs), with 12 million new cases annually. About 3 million teenagers contract an STD each year, and many will have long-term health problems as a result. Women and adolescents are particularly vulnerable to these diseases and their health consequences. In addition, STDs increase the risk of HIV transmission. The Hidden Epidemic examines the scope of sexually transmitted infections in the United States and provides a critical assessment of the nation's response to this public health crisis. The book identifies the components of an effective national STD prevention and control strategy and provides direction for an appropriate response to the epidemic. Recommendations for improving public awareness and education, reaching women and adolescents, integrating public health programs, training health care professionals, modifying messages from the mass media, and supporting future research are included. The book documents the epidemiological dimensions and the economic and social costs of STDs, describing them as \

Increasing Uptake of COVID-19 Vaccination Through Requirement and Incentive Programs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
As the COVID-19 pandemic enters its third year, the emergence of highly transmissible variants has elevated the urgency of increasing vaccine uptake. Accordingly, decision makers nationwide have been implementing various interventions, such as COVID-19 vaccine requirement and incentive programs for specific populations, to increase vaccine uptake. It is important to stress that such programs need to address equitable access to vaccines. Further, while incentives have not proven consistently to be effective in the United States as a means of promoting uptake of first doses of the COVID-19 vaccines, they may have potential for impact if used for booster doses. This rapid expert consultation draws on the fields of behavioral economics, health behavior, risk communication, and psychology to identify actionable guidance for state and local decision makers engaged in designing COVID-19 vaccine requirement and incentive programs to increase uptake of COVID-19 vaccines.

Critical Findings on COVID-19: Select Publications from the National Academies of Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
For more than 150 years, the National Academies of Sciences, Engineering, and Medicine have issued reports detailing leading research on public health and infectious disease. In response to the global outbreak of COVID-19 in 2020, the National Academies has continued this work by issuing publications related to disease transmission, preventative measures, vaccinations, and more that can inform the public response to the pandemic. Critical Findings on COVID-19 includes summaries and highlights of many of our key publications on COVID-19, including consensus study reports, workshop and webinar proceedings, and rapid expert consultations.